The contents of artificial and natural radionuclides in tissues of the Percidae fish from the Dnipro Reservoir - Ananieva, T.; Ананьєва, Таміла Володимирівна; Shapovalenko, Z.; Шаповаленко, З. (My University, 2019)
The purpose of paper was investigation of the contents and tissue distribution of artificial and natural radionuclides of 137Cs, 90Sr, 226Ra, 232Th, and 40K in common perch Perca fluviatilis and pikeperch Sander lucioperca from two fishing areas with various conditions of hydrology and anthropogenic contamination in the Dnipro (Zaporizhzhia) Reservoir. Methods. Totally, 3 kg of investigated fish were selected by research control catches, 10 averaged samples of each type tissues (muscles, bones, gill petals, and scales) were prepared for radiometric assays. Preliminary the samples of biological tissues were crushed with a scalpel, and dried at 105°C to attain a constant weight to concentrate the radioactive elements contained. In dry samples of 5–10 g weighing the specific activity of radionuclides was determined using an SEG-001 “AKP-C” gamma-ray energy scintillation spectrometer and SEB-01-150 beta-radiation spectrometer (Ukraine) in Bq/kg of wet weight, taking into account the coefficient of shrinkage. Digital data were processed by Microsoft Excel 2010, The significant differences between paired values was assessed using Student's t-factor at p<0.05. Findings. It had been found that the radioactive elements of both natural and artificial origins were concentrated greatly in common perch tissues compared to pikeperch. The bone and muscle tissues contained the maximal levels of radionuclides, while respectively smaller amounts of radionuclides were found in gills and scales. The radionuclide levels in the tissues of investigated fish species were significantly higher in the Dnipro Reservoir area with weak flowage and slow water exchange. Originality. The work was performed within the framework of scientific radioecological monitoring of the ichthyofauna in the Dnipro Reservoir. The paper contains unique data for 2018 on the contents of radioactive elements in the commercial Percidae fishes, that allows to draw conclusions about the radiation situation in the hydroecosystem. Practical value. The performed scientific works is a part of modern integral ecological task on providing a human with a set of material and intangible services – natural resources and healthy environments. Мета роботи – дослідити вміст і розподіл по тканинах судака звичайного і окуня річкового основних дозоформуючих радіонуклідів штучного і природного походження (137Cs, 90Sr, 226Ra, 232Th, 40K) на двох рибопромислових ділянках Дніпровського (Запорізького) водосховища, що розрізняються за гідрологічними умовами і характером антропогенного забруднення. Методика. Проби досліджуваних видів риб вагою 3 кг відбирали під час наукового контрольного лову. Для радіометричного аналізу готували по 10 зразків кожного типу біологічних тканин (м’язової, кісткової, зябрових пелюсток, луски). Відібрані тканини подрібнювали, зважували і висушували при 105°C до постійної ваги для концентрування радіоактивних елементів. У висушених зразках вагою 5–10 г вимірювали питому активність радіонуклідів на сцинтиляційних спектрометрах енергій гама- і бета-випромінювань СЕГ-001 АКП-С та СЕБ-01-150 (Україна) у Бк/кг сирої природної ваги (з урахуванням коефіцієнтів усушки). Отримані цифрові дані піддавали статистичному опрацюванню за допомогою Microsoft Excel 2010. Достовірні відмінності між парними величинами оцінювали за t-критерієм Стьюдента при p<0,05. Результати. Виявлено, що радіоактивні елементи як природного, так і штучного походження нагромаджувалися більш значною мірою в тканинах окуня у порівнянні з судаком. У кістковій і м’язовій тканинах знайдені максимальні рівні вмісту радіонуклідів, у той час як у зябрах і лусці концентрації радіонуклідів були порівняно невисокими. Рівні вмісту радіонуклідів у тканинах досліджуваних видів риб значно переважали у ділянці Дніпровського водосховища зі слабкою течією та уповільненим водообміном. Наукова новизна. Робота виконана у межах наукового радіоекологічного моніторингу іхтіофауни Дніпровського водосховища і містить унікальні дані 2018 р. щодо вмісту радіоактивних елементів у промислових рибах родини Percidae, які дозволяють робити висновки про радіаційну ситуацію в гідроекосистемі. Практична значущість. Виконана наукова робота є складовою інтегральної сучасної екологічної задачі щодо забезпечення людини сукупністю матеріальних і нематеріальних благ – природними ресурсами та здоровим довкіллям.
Вміст штучних і природних радіонуклідів у тканинах окуневих риб Дніпровського водосховища
Keywords: artificial radionuclides; штучні радіонукліди; natural radionuclides; природні радіонукліди; common perch; окунь; pikeperch; судак; specific activity; питома активність; the Dnipro (Zaporizhzhia) Reservoir; Дніпровське (Запорізьке) водосховище